2013
DOI: 10.1186/1743-7075-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imiglucerase on the growth and metabolism of Gaucher disease type I patients: a systematic review

Abstract: BackgroundGaucher disease (GD) type I is the most common type of GD. Its main clinical manifestations are hepatosplenomegaly as well as bone and hematological abnormalities. The objective of the present study was to perform a literature review on the growth and metabolism of GD type I patients.MethodsWe searched Pubmed and Scielo.br databases with predetermined study limits: case series (n≥5), clinical trials, systematic reviews, and meta-analyses, and enzyme replacement therapy (ERT) with alglucerase or imigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The clinical variability found in patients with GD is related to the type of mutation in the GBA gene and to the proteins, substrates and metabolism of each individual, as well as environmental factors; yet, many of these factors are not completely known. [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical variability found in patients with GD is related to the type of mutation in the GBA gene and to the proteins, substrates and metabolism of each individual, as well as environmental factors; yet, many of these factors are not completely known. [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…63 Growth deceleration occurs between 3 and 5 years of age and height increase diminishes in later childhood; however at the end of the growth period the difference between the final and the target height were not significant. 13 Therefore, numerous studies have investigated the impact of imiglucerase on growth retardation. 64 In 2008, Andersson et al determined the effects of long-term ERT with alglucerase or imiglucerase on linear growth.…”
Section: Clinical Trials and Data From The Icgg Gaucher Registrymentioning
confidence: 99%
“…However, in our series, patients experienced BMR increases of up to 70%, which suggests that pulmonary involvement may be a contributing factor to these abnormalities in energy metabolism rather than their sole cause. Studies have shown that patients with GD type I also exhibit a hypermetabolic state, the causes of which remain unclear (Barton et al 1989;Corssmit et al 1995;Doneda et al 2011Doneda et al , 2013. The two patients in our series with pulmonary involvement and a more severe phenotype also had comparatively marked hypermetabolism.…”
Section: Discussionmentioning
confidence: 55%